Improvement of foamed part surface quality with variothermal temperature control and analysis of the mechanical properties. (September 2019) - Hopmann, Christian; Lammert, Nicolai; Zhang, Yuxiao
Thermoplastic foam injection molding offers various advantages for both processing and product design. Despite its many benefits, the moderate surface quality still constitutes a major disadvantage of this process. A variothermal mold temperature control enables the improvement of the surface quality. Different dynamic temperature control strategies are employed and analyzed regarding their effectiveness and scope of application. Mold temperatures above the specific material transition temperatures allow the surface defects to be cured and enable the production of foamed thermoplastic parts with surface qualities comparable to those of the compact reference samples. The high mold temperatures during the injection phase alter the foam structure and the skin layer thicknesses, which impacts the mechanical properties.